U.S.-Mexico Relations: Trends and Issues (International relations and international law Journal, 2016)
The United States and Mexico are more than neighbors sharing a common border. The United States and Mexico are economic partners, often political allies, and sometimes competitors for talent, capital, and technologies. Economic interconnection and the density of cross-border interaction have shaped mutual relations for a long time. This paper considers the following issues: assessing Obama’s Latin America Policy, U.S.-Mexico relationship in the Obama Administration; and, potential areas of collaboration between the United States and Mexico. The goal of this paper is to examine the recent development of bilateral US-Mexican cooperation and identify major areas but also limits of interaction.
Keywords: cooperation; the Obama administration; Latin America; US-Mexico relations; Trans-Pacific Partnership; NAFTA; Mеrida Initiative